Posterior Shoulder Capsules Are Thicker and Stiffer in the Throwing Shoulders of Healthy College Baseball Players: A Quantitative Assessment Using Shear-Wave Ultrasound Elastography. (December 2015) - Takenaga, Tetsuya; Sugimoto, Katsumasa; Goto, Hideyuki; Nozaki, Masahiro; Fukuyoshi, Masaki; Tsuchiya, Atsushi; Murase, Atsunori; Ono, Tetsuya; Otsuka, Takanobu
Background: Posterior and posteroinferior capsules in the shoulder joints of throwing athletes have been reported to be thicker in throwing than nonthrowing shoulders, and this has a relationship to glenohumeral internal rotation deficit (GIRD). However, the stiffness of these thickened capsules has not been reported. Shear-wave ultrasound elastography is a new technology that can measure tissue elasticity quantitatively. Hypothesis: The posterior and posteroinferior capsules are stiffer as well as thicker in the throwing shoulders of baseball players than in their nonthrowing shoulders. The thickness and elasticity of these capsules are inversely correlated with glenohumeral internal rotation. Study Design: Cross-sectional study; Level of evidence, 3. Methods: Forty-five male college baseball players were examined. The thickness and elasticity of the posterior capsule beneath the infraspinatus and the posteroinferior capsule beneath the teres minor were measured using an ultrasonic device equipped with shear-wave elastographic technology. Glenohumeral internal rotation at 90° of shoulder abduction and humeral retrotorsion were also measured. Results: The mean thickness and elasticity of the posterior capsule were significantly greater for the throwing compared with the nonthrowing shoulder (thickness: 1.34 vs 1.04 mm, respectively; elasticity: 40.0 vs 32.2 kPa, respectively; P < .001 for both). The mean thickness and elasticity of the posteroinferior capsule were also significantly greater in the throwing compared with the nonthrowing shoulder (thickness: 1.40 vs 1.04 mm, respectively; elasticity: 39.4 vs 31.6 kPa, respectively; P < .001 for both). After correcting the range of motion for bilateral differences in retrotorsion, correlation coefficients showed that posterior capsule thickness and elasticity (Pearson r = −0.43 and −0.56, respectively; P < .001 for both) and posteroinferior capsule thickness and elasticity (Pearson r = −0.51 and −0.52, respectively; P < .001 for both) were negatively correlated with the corrected glenohumeral internal rotation. Bilateral differences in posterior and posteroinferior capsule elasticity correlated with bilateral differences in the corrected glenohumeral internal rotation (Pearson r = 0.46 [ P = .0015] and 0.48 [ P < .001], respectively), whereas bilateral differences in posterior and posteroinferior capsule thickness did not (Pearson r = −0.13 [ P = .38] and 0.17 [ P = .28], respectively). Conclusion: The posterior and posteroinferior capsules were stiffer as well as thicker in the throwing shoulder of college baseball players compared with the nonthrowing shoulder. Posterior capsule elasticity appeared to have a greater effect on GIRD than did posterior capsule thickness. This technology could be used as a noninvasive screening method for throwing athletes to identify players at potential risk of shoulder injuries.